The relationship between maternal knowledge about nutrition and abstinence behavior during postpartum eating in the work area of Uptd Puskesmas Simpang Kiri of Subulussalam City Year 2025 - Fitriani Bancin; Rahayu Ningsih; Ricca Nophia Amra; Ira Sanjaya; Irnawati Irnawati; Desi Handayani Lubis (Science Midwifery, 2025)
In Indonesia, there are still many postpartum mothers who abstain from eating during the postpartum period, out of 4,406,437 postpartum mothers who abstain from eating, which is as much as 86%. Abstaining from eating is a term used to describe a person's practice of not consuming certain foods due to cultural prohibitions passed down from generation to generation. The purpose of this study is to determine the relationship between maternal knowledge about nutrition and the behavior of abstinence from postpartum eating in the Work Area of the UPTD Puskesmas Simpang Kiri, Subulussalam City in 2025. This study is correlational analytics with a cross sectional approach using primary data and secondary data. The population in this study is all postpartum mothers in the Work Area of the UPTD Simpang Kiri Health Center. The sampling technique in this study used Total sampling, with a sample of 32 respondents and the measuring tool used was a questionnaire. The results of the study using the chi-square test obtained a result of 0.000 <0.05, so it can be concluded that there is a relationship between maternal knowledge about nutrition and the behavior of abstinence from postpartum eating in the UPTD Puskesmas Simpang Kiri Work Area of Subulussalam City in 2025. It is hoped that health workers, especially midwives, can further improve the quality of midwifery services, one of which is by increasing counseling on nutrition during the postpartum period.